Budget support as an aid instrument: neither pandemonium nor panacea - Stefan Leiderer (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Programme-based approaches, including sector and general budget support, are core elements of the Paris Agenda for more effective aid. This agenda emerged from an intense international debate that has since the mid 1990s centred mainly on modalities and instruments best suited to improving the effectiveness of international development aid. Yet, budget support continues to be a highly contentious issue in Germany's and other donor countries' development policy debates. While in development cooperation practice, budget support has evolved into a fairly well established instrument to support poverty reduction strategies in developing countries, the broader political debate on the topic is generally ill-informed. In practice, there is a broad consensus that budget support is suited only for a limited group of countries, that it should always be used in conjunction with other instruments, and that the instrument's potential benefits need to be weighed against possible risks. As a consequence, in many donor countries budget support continues to account for only a minor share of bilateral aid (2.5 % of German bilateral commitments in 2008). Despite widespread scepticism, budget support has evolved into a reasonably well-established aid instrument in a number of developing countries, arguably with positive effects at least with respect to donor coordination and alignment to country strategies and systems. In addition, early experiences and evaluations confirm that budget support can be an effective instrument when it comes to strengthening the quality of policy dialogue, transparency and accountability in budget management, and enhancing donor coordination. At present, however, there are hardly any robust studies of the instrument's concrete effects on poverty. At the same time, there is a growing discussion on the use of budget support to finance goals other than the Millennium Development Goals (MDGs), such as adaptation to climate change. This would risk the instrument's potential effectiveness for development. A central challenge for development cooperation is therefore the need to develop adequate evaluation methods for budget support. Another is to ensure that the instrument is not overloaded with new demands and goals. This will pose a conceptual and political challenge for German development cooperation.
Keywords: 330